Potential capacities of actinobacteria in pest control in ecological agriculture - Volosciuc, L.; Lungu, A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Excessive use of synthetic pesticides causes, in addition to the effect on non-target organisms, problems associated with the accumulation of toxic residues and metabolites, environmental pollution and disruption of ecological balance. This necessitates researching and highlighting effective and harmless methods and means of controlling pests, among which a special place belongs to biological means of protection, in particular biological products. The use of biological insecticides developed on the basis of actinobacteria has demonstrated high biological efficiency, significant environmental and economic effectiveness. The article presents a laboratory and field evaluation of the antifungal activity of Streptomyces actinomycetes strains by inhibiting the growth and development of Fusarium pathogens. The biological characteristics and technological indicators of Saccharopolyspora spinosa biomass production for pest control in protected ground were determined.